1970
DOI: 10.3329/jbcps.v26i1.4227
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Hypomagnesemia in Hospitalized Diabetic Hypokalemic Patients

Abstract: Recent studies suggest that there is strong relationship between serum magnesium and diabetes. Low serum magnesium is one of the risk factors of diabetes mellitus and its complications, at the same time diabetes is one of the common causes of hypomagnesemia. Hypokalemia is also quite common in diabetic patient. When hypokalemia coexists with hypomagnesemia, the chance of ‘complications of hypokalemia' increase significantly. In addition, the correction of hypokalemia becomes difficult. However, the exact frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…found a mean diabetic duration of 8.85 years in hypomagnesemic patients and concluded that serum magnesium level has no direct relationship with diabetic duration if the diabetes is well controlled. [13]…”
Section: Discussionmentioning
confidence: 99%
“…found a mean diabetic duration of 8.85 years in hypomagnesemic patients and concluded that serum magnesium level has no direct relationship with diabetic duration if the diabetes is well controlled. [13]…”
Section: Discussionmentioning
confidence: 99%
“…In one study frequency was much higher, 63.3%. 17 In another study, prevalence was 42% in malnutrition related diabetes mellitus patients. 18 Conclusion From this study, it was found that hyponatraemia, hypokalaemia and hypomagnaesemia were common electrolyte imbalance in hospitalized diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 It has been observed that the raised HBA1C and lipoprotein levels in current series directly proportional to hyperglycemia, insulin resistance and uncontrolled diabetes mellitus due to magnesium deficiency, the observations are consistent with the findings reported by Srinivasan et al 28 The present study results suggested that low magnesium levels are associated with the duration of diabetes and foot ulcers; and the Haquea et al study found the strong relationship between diabetes mellitus and its duration. 29 Furthermore it has been detected the low serum magnesium level is responsible for persistent hyperglycemia and dyslipidemia leads to atherosclerosis and that is again risk factor for peripheral vascular disease and foot ulceration. 30 Hypomagnesemia again directly proportional to blood pressure, oxidative stress and thickness in carotid vasculatures and ischemic heart diseases.…”
Section: Discussionmentioning
confidence: 99%